Insects involved in decomposing corpses in the Constantine region-Algeria - Benkenana Naima (Open Journal of Trauma - Peertechz Publications, 2020)
Forensic entomology is based on the use of scavenging insects to estimate the time of death in the course of judicial inquiries and allows in some cases specify the circumstances of death. This technique is based on solid scientific basis and is now commonly used as part of criminal cases. This process involves the chemical and physical breakdown of tissue by microorganisms such as fungi and bacteria. The decomposition of animal body, it is known that there are five stages; fresh corpse, rot, fermentation, dehydration and skeleton. Tracking all stages of decomposition of dog body in the period from 15 February to 26 April 2018. With the collection of 1135 insects (whole individuals and larvae) over the animal's corpse and around it, 21 insects belonging to three  orders were identified: Diptera, Coleoptera and Hymenoptera. The results of this study add data to forensic entomology in Algeria and its potential for use in judicial investigations.